Cardiac outcomes in a cohort of adult survivors of childhood and adolescent cancer: retrospective analysis of the Childhood Cancer Survivor Study cohort. (8th December 2009) - Mulrooney, Daniel A; Yeazel, Mark W; Kawashima, Toana; Mertens, Ann C; Mitby, Pauline; Stovall, Marilyn; Donaldson, Sarah S; Green, Daniel M; Sklar, Charles A; Robison, Leslie L; Leisenring, Wendy M
Abstract : Objectives To assess the incidence of and risks for congestive heart failure, myocardial infarction, pericardial disease, and valvular abnormalities among adult survivors of childhood and adolescent cancers. Design Retrospective cohort study. Setting 26 institutions that participated in the Childhood Cancer Survivor Study. Participants 14 358 five year survivors of cancer diagnosed under the age of 21 with leukaemia, brain cancer, Hodgkin's lymphoma, non-Hodgkin's lymphoma, kidney cancer, neuroblastoma, soft tissue sarcoma, or bone cancer between 1970 and 1986. Comparison group included 3899 siblings of cancer survivors. Main outcome measures Participants or their parents (in participants aged less than 18 years) completed a questionnaire collecting information on demographic characteristics, height, weight, health habits, medical conditions, and surgical procedures occurring since diagnosis. The main outcome measures were the incidence of and risk factors for congestive heart failure, myocardial infarction, pericardial disease, and valvular abnormalities in survivors of cancer compared with siblings. Results Survivors of cancer were significantly more likely than siblings to report congestive heart failure (hazard ratio (HR) 5.9, 95% confidence interval 3.4 to 9.6; P<0.001), myocardial infarction (HR 5.0, 95% CI 2.3 to 10.4; P<0.001), pericardial disease (HR 6.3, 95% CI 3.3 to 11.9; P<0.001), or valvular abnormalities (HR 4.8, 95% CI 3.0 to 7.6; P<0.001). Exposure to 250 mg/m 2 or more of anthracyclines increased the relative hazard of congestive heart failure, pericardial disease, and valvular abnormalities by two to five times compared with survivors who had not been exposed to anthracyclines. Cardiac radiation exposure of 1500 centigray or more increased the relative hazard of congestive heart failure, myocardial infarction, pericardial disease, and valvular abnormalities by twofold to sixfold compared to non-irradiated survivors. The cumulative incidence of adverse cardiac outcomes in cancer survivors continued to increase up to 30 years after diagnosis. Conclusion Survivors of childhood and adolescent cancer are at substantial risk for cardiovascular disease. Healthcare professionals must be aware of these risks when caring for this growing population.